Learner-Centered Approach to Students - Yu.B., Nadtochiy; Nadtochiy, Yuliya B. (The journal of contemporary issues in business and government, 2021)
For domestic pedagogy, the concepts of ‘learner-centered education’ and ‘learner-centered approach’ are no longer new. Can the learner-centered approach (style of interaction) be applied to students in higher education institutions? Or it may only be possible in preschool education institutions or in general education institutions? A many years’ experience in applying the learner-centered approach to pupils (students) in practice shows that such approach has been effective at all levels of general and vocational education. This article discusses the specifics of the implementation of the learner-centered approach in the sphere of higher education, presents the criteria and indicators of such approach as well as the results of the student survey aimed at identifying the type of pedagogical interaction used.